THE ROLE OF TIMUR AND THE TIMURIDS IN THE DEVELOPMENT OF ARCHITECTURE OF CENTRAL ASIA - Nurmukhamedova Shoira; Abduvakhobova Madina (Modern American Journals, 2025)
This paper examines the role of Amir Temur and the Timurids in the formation of Central Asian architecture. It reveals the features of the construction culture using examples of civil and religious architecture.
Keywords: Amir Temur, Timurids, monumental structures, civil structures, imperial style, khonakokh, gurkhana, tim.